Influence of TiO2- and ZrO2-addition on the interaction of alumina castable with molten coal and gasifier slag. (15th June 2015) - Gehre, Patrick; Aneziris, Christos G.; Klinger, Mathias; Schreiner, Marcus; Neuroth, Markus
Highlights: ZrO2 and TiO2 has found to improve the corrosion resistance of alumina refractory. In situ formation of spinel layer protects AZT castables during corrosion. In CO/H2 atmosphere much higher corrosion can be observed compared to CO atmosphere. AZT refractories mark prospective lining materials for gasifiers producing syngas. AZT refractories are potential to replace chromia materials as lining for gasifiers. Abstract: Gasification is a key process of chemical and energy industry. In order to improve the economic feasibility of gasifiers, new refractory lining materials with a long service life have to be developed, which can substitute the currently used high chromia bricks. TiO2 and ZrO2 were added to an Al2 O3 -refractory in order to improve its thermal shock and corrosion resistance against molten slags. Next to the investigation of material properties and structure, cup tests with holding time of 3 and 150 h at 1450 °C in different gasification-similar reducing atmospheres have been performed and the corrosion mechanism identified by analysing the slag–refractory interface in SEM. During sintering, the addition of 2.5 wt.% TiO2 causes the formation of needle-shaped Na2 Al2 Ti6 O16 crystals, which essentially influence the microstructure and provide excellent thermal shock resistance. In addition, in contact with coal slag, the presence of titania and zirconia promotes the formation of a protective MgAl2 O4 -layer, which stops slag infiltration and dissolution.